Noise in reconstructive tomography - Espinosa E., Ismael (Revista Mexicana de Ingenieria Biomedica, 2018)
The purpose of this paper is to analize those aspects which determine the ability of Reconstructive or Computer-assited Tomography to distinguish quantitatively minute differences in X-ray attenuation conefficients, when passing through living tissues. We aim to characterize the different sources of noise and the uncertainties in the determination of these coefficients, as well as the means of diminishing or elliminating this noise. A detailed analysis of the available literature is made. We present the expressions which allow for the evaluation of the linear attenuation coefficient variance, and furnish the guidelines in order to get a smaller value of this variance.